Antegrade transpapillary biliary stent placement via endosonography‐guided choledochoduodenostomy for treatment of recurrent cholangitis. Issue 4 (20th February 2022) - van Wanrooij, Roy L. J.; Voermans, Rogier P.; Fockens, Paul
Abstract : Watch a video of this article.